Expression of hypoxia-inducing factor-1α and matrix metalloproteinase-9 in the recipient parasylvian cortical arteries with different hemodynamic sources in adult moyamoya disease - Luo, Mingrui; Yu, Jin; Xin, Can; Hu, Miao; Tao, Tianshu; Wan, Guiping; Chen, Jincao; Zhang, Jianjian (Frontiers in Surgery, 2023)
Objective: In our latest research, we have demonstrated that the recipient parasylvian cortical arteries (PSCAs) with hemodynamic sources from the middle cerebral artery (M-PSCAs) has a higher risk of postoperative cerebral hyperperfusion (CHP) syndrome than those from non-M-PSCAs in adult moyamoya disease (MMD) patient. However, whether there are differences between M-PSCAs and non-M-PSCAs in vascular specimens characteristics has not been studied. In this study, we further investigate the vascular specimens of recipient PSCAs by histological and immunohistochemical methods. Methods: 50 vascular specimens of recipient PSCAs were obtained from 50 adult MMD patients during the combined bypass surgeries in our departments of Zhongnan hospital. 4 recipient PSCAs samples were also obtained in the same way from the middle cerebral artery occlusion patients. The samples were received the pathological sectioning, hematoxylin and eosin staining, and immunohistochemistry, then the vascular wall thickness, matrix metalloproteinase-9 (MMP-9) and hypoxia-inducing factor-1α (HIF-1α) were analyzed. Results: M-PSCAs adult MMD patients had a thinner intima than non-M-PSCAs in the recipient PSCAs specimens. In recipient non-M-PSCAs vascular specimens, the immunoreactivity indicating HIF-1α and matrix metalloproteinase-9 (MMP-9) was significantly higher than M-PSCAs groups. The logistic regression analyses showed that the M-PSCAs was an independent risk factor of postoperative cerebral hyperperfusion (CHP) syndrome (OR 6.235, 95% CI1.018-38.170, P= 0.048) in MMD. Conclusion: Our results indicate that M-PSCAs adult MMD patients had thinner intima than non-MCAs adult MMD patients in the PSCAs. In addition, HIF-1α and MMP-9 were overexpressed in non-M-PSCAs vascular specimens.